Sistem Pakar Diagnosa Penyakit Lambung Menggunakan Metode Forward Chaining Dan Certainty Factor - Scheryl Pongantung; Marline Sofiana Paendong; Luther Alexander Latumakulita (Faculty of Mathematics and Natural Sciences Sam Ratulangi University, 2024)
Limited knowledge about the early symptoms of stomach diseases has motivated the author to develop a system that helps the community obtain information. This system aims to provide assistance to the public in obtaining information, consultation, and early treatment for stomach diseases without having to have direct meetings with experts. The expertise of a medical professional in diagnosing stomach diseases can be implemented into an application. In this Expert System, Forward Chaining method is used for reasoning and the Certainty Factor method is used to calculate confidence levels. Based on data processing from one of the users, the research results show that GERD is the most likely diagnosis, with a Certainty Factor value of 96.5%.